Development of E-module through Google Site to Improve Students’ Grammar Ability - Majri, Sajid Wijdan; Ardiya, Ardiya; Niah, Siti (FKIP-Universitas Riau, 2024)
The purpose of this study is to develop an e-module through Google Site to improve students’ grammar ability and to determine the significant impact of it for students at class X of SMKN 4 Pekanbaru. This research was conducted in 3 months (January-March 2024) involving class AKL3 which amounted to 31 students. The results showed that students in the class as samples, who were assessed using Google Site application, demonstrated higher levels of grammar mastery compared to their grammar ability before the students receive the researcher’s instruction, indicating a significant positive effect. The result of the students’ grammar test was improved in the quality of their grammar ability measured by the result of N-gain score which was gained from the pre-test and post-test by using SPSS. In addition, this research can be concluded that the implementation of an electronic learning module via Google Site has improved students' English grammar ability.